RANCANG APLIKASI TOKO JAHIT MAMA ABIL COLLECTION BERBASIS WEBSITE - Muhamad Fahmi Fauzi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Mama Abil Collection sewing shop is a small business specializing in women's fashion garment tailoring services. In order to improve efficiency and responsiveness to customer needs and keep up with technological advancements, this research aims to design a website-based catalog application for Mama Abil Collection sewing shop using the waterfall method.The waterfall method was chosen as the approach for software development due to its structured and organized framework. The development stages included requirements analysis, system design, implementation, testing, and maintenance. The requirements analysis phase involved interviews with the shop owners and customers to understand their needs and expectations for the catalog application. Based on the analysis, a system application was designed to meet those requirements.The catalog application was developed using PHP programming language, utilizing the CodeIgniter framework to expedite the development process. MySQL database was employed to store product data, categories, and customer information. Additionally, HTML, CSS, and JavaScript were utilized to create a responsive and visually appealing user interface.During the testing phase, functionality and reliability tests were conducted to ensure the application performed well and met user requirements. Additionally, user interface testing was performed to enhance the user experience.It is expected that this design of the catalog application will help Mama Abil Collection sewing shop enhance efficiency in managing their product catalog and provide an improved shopping experience for customers. The application is envisioned to enhance the competitiveness of the sewing shop in the digital era.